Component layout optimization design based on genetic algorithm. (September 2019) - Shen, B; Pan, Z W; Lin, H; Li, W Z
Abstract: When working, electronic equipment is often subjected to a mechanical environment dominated by vibration. The printed circuit board (PCB) in the equipment is prone to deformation and transmits vibration to the components on the board. As the weakest link, the component corner position has a large acceleration, which is one of the important reasons for the failure of components and the entire electronic equipment. Based on the finite element modeling of PCB, the interaction between the finite element analysis software NASTRAN and the programming software MATLAB is realized, and the application of genetic algorithm in component layout optimization becomes possible. The optimization results show that the method adopted in this paper can effectively reduce the acceleration value at the component corner and optimize the mechanical environment when the electronic equipment works.